2022
DOI: 10.1002/er.8219
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of electric vehicle charging duration time using ensemble machine learning algorithm and Shapley additive explanations

Abstract: Summary Electric vehicles (EVs) are the most important components of smart transportation systems. Limited driving range, prolonged charging times, and inadequate charging infrastructure are the key barriers to EV adoption. To address the problem of prolonged charging time, the simple approach of developing a new charging station to enhance the charging capacity may not work due to the limitation of physical space and strain on power grids. Prediction of precise EV charging time can assist the drivers in effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…A variety of ensemble approaches were used in a recent study on demand prediction to anticipate the charging time for EVs [ 26 ]. Eddine et al [ 27 ] suggested a new deep learning method for charging demand predicting for EVs that achieved good prediction results by experimenting with two datasets.…”
Section: Related Workmentioning
confidence: 99%
“…A variety of ensemble approaches were used in a recent study on demand prediction to anticipate the charging time for EVs [ 26 ]. Eddine et al [ 27 ] suggested a new deep learning method for charging demand predicting for EVs that achieved good prediction results by experimenting with two datasets.…”
Section: Related Workmentioning
confidence: 99%
“…XGBoost, AdaBoost, and Bagging were the employed soft computing techniques (Shen et al, 2022). The research by Ullah et al (2022) used four different ensemble machine learning (EML) algorithms: random forest, XGBoost, categorical boosting, and light gradient boosting machine, for predicting EVs' charging time. Mao et al (2022) developed a stacked generalization (stacking)-based incipient fault diagnosis scheme for the traction system of high-speed trains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green transportation is essential to address climate change mitigation since they minimize CO 2 and other pollutants that are frequently used in conventional vehicles [12,13]. Amongst all green transportation choices, e-bikes, shared mobility, electric vehicles (EVs), and bus rapid transit are an intriguing option for addressing the aforementioned challenges [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Charging infrastructures are becoming crucial components for adopting EVs, connected to vehicle technology and efciency and the accessibility of a reliable power supply to charging stations [12]. It is also tied with the increased electricity demand in other sectors [19].…”
Section: Introductionmentioning
confidence: 99%